2013
DOI: 10.1021/ic4003884
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Magnetochemical Overparametrization, Exemplified by One-Dimensional Chains of Hexanuclear Iron(III) Pivalate Clusters

Abstract: One-dimensional chain coordination polymers based on hexanuclear iron(III) pivalate building blocks and 1,4-dioxane (diox) or 4,4'-bipyridine (4,4'-bpy) bridging ligands, [Fe6O2(O2CH2)(O2CCMe3)12(diox)]n (1) and [Fe6O2(O2CH2)(O2CCMe3)12(4,4'-bpy)]n (2), showcase the utility of the angular overlap model, implemented in the program wxJFinder, in the predictive identification of the relative role of intra- and intercluster coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Since 1-4 are each composed of eight centers, the total number of exchange interaction parameters J ij is 28 ((n − 1)n/2). To reduce the number of independent parameters, the computer program wxJFinder 10,12 has been used to determine which of the interactions are negligible or may be treated as identical. Adopting the ideas of Weihe and Güdel 13a as well as Werner et al, 13b the calculations of wxJFinder are based on the angular overlap model (AOM) taking into account various experimental datasets for compounds containing oxo-bridged Fe III centers.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 1-4 are each composed of eight centers, the total number of exchange interaction parameters J ij is 28 ((n − 1)n/2). To reduce the number of independent parameters, the computer program wxJFinder 10,12 has been used to determine which of the interactions are negligible or may be treated as identical. Adopting the ideas of Weihe and Güdel 13a as well as Werner et al, 13b the calculations of wxJFinder are based on the angular overlap model (AOM) taking into account various experimental datasets for compounds containing oxo-bridged Fe III centers.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…We have recently demonstrated that in the case of µ 2+m -O-bridged Fe III centers, the angular overlap model (AOM) can reliably assess inter-and intra-cluster interactions in hexanuclear Fe III pivalate clusters [Fe 6 O 2 (O 2 CH 2 )(O 2 CCMe 3 ) 12 ] bridged into 1D chains by 1,4-dioxane or 4,4′-bipyridine spacers. 10 To obtain reasonable initial values of the exchange coupling constants for the fitting routines of CONDON 2.0, 11 we introduced the program wxJFinder, 10,12 which combines AOM and structural information by extending the concepts of Weihe et al 13a and Werner et al 13b We herein demonstrate this approach on more complex Fe III 14 with triethanolamine (teaH 3 ) or N-methyldiethanolamine (mdeaH 2 ) under various reaction conditions. Christou et al 15 reported the first similar {Fe 8 } benzoate cluster with teaH 3 , [Fe 8 O 3 (O 2 CPh) 9 (tea)(teaH) 3 ]•MeCN, and this motif has been extended by Murray et al 16 and Powell et al 17 to a series of {Fe 8 } disk-like propionate and pivalate clusters of the general formula [Fe 8 O 3 (O 2 CR) 6 (tea)(teaH) 3 (L) 3 ]•solvent, where R = CH 2 Me, L = F; 16 R = CMe 3 , L = N 3 or SCN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using stable nitronyl nitroxide radicals, Ovcharenko et al bridged {Mn 6 O 2 } pivalate clusters into a diamond-like network. Other efforts in the preparation of coordination polymers from μ-oxo manganese or iron polynuclear carboxylates led to the formation of 1D chains or 2D layers: chains composed of trinuclear {Mn 3 O}, {Fe 3 O}, and {Fe 2 MO} (M = Mn, Co, Ni), tetranuclear {Mn 4 O 2 } and {Fe 4 O 2 }, or hexanuclear {Mn 6 O 2 } , and {Fe 6 O 2 } carboxylate clusters and layers that are built up from homometallic {Fe 3 O} or heterometallic {Fe 2 MO} (M = Mn, Co, Ni , ) trinuclear carboxylate clusters. For the first time, the combination of a hexanuclear ferric pivalate cluster, [Fe 6 O 2 (OH) 2 (O 2 CCMe 3 ) 12 ], with N-donor ligands in solvothermal reactions, which have been demonstrated to be the best method of synthesizing crystalline materials, resulted in the formation of MOFs, namely {[Fe 3 O­(O 2 CCMe 3 ) 6 (4,4′-bpy) 1.5 ]­(OH)·0.75­(CH 2 Cl 2 )· x­( H 2 O)} n ( 1 ) and {[Fe 2 CoO­(O 2 CCMe 3 ) 6 (bpe) 0.5 (pyz)]} n ( 2 ) (where 4,4′-bpy = 4,4′-bipyridine; bpe = 1,2′-bis­(4-pyridyl)­ethylene; pyz = pyrazine).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to hexanuclear {Mn6(μ4-O)2} building blocks, the use of hexanuclear {Fe6(μ3-O)2} building blocks in the design of CCPs is fairly scarce. Until now, only two such compounds have been published [52]. 1D zigzag chain coordination polymers [Fe6O2(O2CH2)(piv)12(diox)]n (15) ( Figure 7 (19) were prepared from the reaction of a simple [Mn(piv)2] salt (18) or a hexanuclear [Mn6(is)12(His)6] isobutyrate cluster (19) and the bent, semi-rigid N,N′-donor aldrithiol (adt-4) spacer ligands in thf.…”
Section: Oxo-tetranuclear Mn/fe-based Ccpsmentioning
confidence: 99%